Clinical symptoms and related factors of obstructive sleep apnea among overweight and obese taxi drivers (Medical Journal of Indonesia, 2015)
Background: Obstructive sleep apnea (OSA) is common condition in commercial drivers while overweight and obesity as the most important risk factors. This study aimed to know the clinical symptoms and risk factors of OSA in overweight and obese taxi drivers in Jakarta, Indonesia. Methods: A cross-sectional study was done in 103 taxi drivers in Jakarta from November 2011–September 2013, by systematic random sampling from 10 taxi stations. Inclusion criteria were taxi drivers with body mass index (BMI) which 23–29.9 and mild or moderate OSA. Portable polysomnography (PSG) test was used to diagnose OSA. Parametric and nonparametric test were used in bivariate analysis. Logistic regression multivariable was used to final evaluate risk factors of OSA. Results: There were 54 (52.4%) of 103 drivers with OSA and 49 (47.6%) without OSA. Clinical symptoms found significantly (p<0.05) were snoring, unrefreshing sleep, occasional sleep while driving, and headache or nausea on waking up in the morning. Risk factors for OSA were increased BMI (OR=0.60, 95% CI=0.45–0.79, p=0.001), snoring history in the family (OR=4.92, 95% CI=1.82–13.31, p=0.002) and sleep duration <7 hours within 24 hours (OR=5.14, 95% CI=1.37–19.23, p=0.015). Conclusion: Clinical symptoms of OSA were snoring, unrefreshing sleep, occasional sleep while driving and headache or nausea on waking up in the morning. Risk factors of OSA were increased BMI, snoring history in the family and sleep duration <7 hours within 24 hours.